Let's Speak Up! Improving the Public Speaking Ability of Karang Taruna Members of Karang Rejo Village, Stabat District, Langkat Regency - Humaizi; Hamdani Harahap; Muhammad Yusuf (CERED Indonesia Institute, 2022)
Public speaking is a skill that should be possessed in this digital era. In addition to being used as a public speaking technique, public speaking is also an indicator or requirement for prospective workers in many companies. The results of the situation analysis showed that members of the Karang Rejo village cadets, Stabat district, Langkat regency, had problems in public speaking skills; Minimal public speaking skills, low level of awareness to hone public speaking skills, and limited access and materials to learn public speaking. Responding to this problem, activities in the form of socialization and assistance in improving public speaking skills were applied to members of the Karang Rejo village cadets. This activity has been completed on August 7, 2021 at the Karang Rejo Village Hall, Stabat district, Langkat regency. In the implementation of this activity, the method of lectures, discussions and questions and answers is applied. The results concluded that the members of the Karang Rejo village cadets were very enthusiastic and interested in developing public speaking skills. They also agree that public speaking skills are a very important skill in this era.